PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VII SMPN 1 SOPPENG RIAJA KABUPATEN BARRU - Mardhiah Mardhiah; Andi Ika Prasasti Abrar; Khadijah Khadijah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
This study aims to find out the description of students 'mathematics learning outcomes in the class using the TAI learning model, the description of students' mathematics learning outcomes in the class using conventional learning models, differences in mathematics learning outcomes for the Team Assisted Individualization (TAI) type of cooperative learning and conventional models , differences in student mathematics learning outcomes in terms of the influence of the ability to understand mathematical concepts in terms of adversity quotient, the effect of the interaction between cooperative learning models of Team Assisted Individualization (TAI) in terms of adversity qutient on the ability of mathematics learning outcomes. This type of research is Quasi Experimental Design. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis with F ANAVA test. The results showed a description of students 'mathematics learning outcomes in the class using the Team Assisted Individualization (TAI) learning model in the medium category, the description of students' mathematics learning outcomes in the class using conventional learning models was in the moderate category, there were differences in mathematics learning outcomes using models Team Assisted Indivisualization (TAI) learning and conventional learning models in class VII students of SMP Negeri 1 Soppeng Riaja, there were no differences in mathematics learning outcomes in terms of adversity quotient class VII students of SMP Negeri 1 Soppeng Riaja, there was no interaction effect between TAI learning models in terms of adversity quotient on the mathematics learning outcomes of class VII students of SMP Negeri 1 Soppeng Riaja. Thus it can be concluded that the TAI learning model influences students' mathematics learning outcomes and mathematics learning outcomes do not depend on the level of adversity quotient of students.